Salt licks and long hunters: an environmental history of the Plains bison east of the Mississippi River - Matullo, Jake, author; Zwick-Tapley, Sarah, advisor; Swetnam, Sunshine, committee member (Colorado State University. Libraries, 2025)
From the 1500s to the early 1800s, hundreds of thousands of bison once lived east of the Mississippi River. This was due to two principle reasons: the clearance of forests by Native Americans for agriculture, and the devastating decline of those same Native Americans at the hand of introduced Old World diseases. With greater open space and reduced hunting and habitat pressure from people, bison crossed the Mississippi and expanded from the Prairie Peninsula into many areas of the east. There, they affected the environment in remarkable ways, such as by improving grassland biodiversity and creating navigable paths in dense forests. Not only did many Native American societies use these paths for travel, but they made various different clothes and tools out of bison as well. Europeans and Americans hunted bison as well, primarily for their meat and hides, ultimately driving them to extinction in the east. Now, many different bison herds have been reestablished out east. However, do they even truly belong there?
Keywords: environmental history; ecology; history; Shifting Baseline Syndrome